2011
DOI: 10.1016/j.jval.2010.10.034
|View full text |Cite
|
Sign up to set email alerts
|

Economic Evaluation of Reamed versus Unreamed Intramedullary Nailing in Patients with Closed and Open Tibial Fractures: Results from the Study to Prospectively Evaluate Reamed Intramedullary Nails in Patients with Tibial Fractures (SPRINT)

Abstract: Our economic analysis from a governmental perspective suggests small differences in both cost and effectiveness with large uncertainty between reamed and unreamed intramedullary nailing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 10 publications
0
15
0
Order By: Relevance
“…One study showed that there was no significant difference in the costs from the index procedure, index hospital stay, and fracture-associated medications; however, the re-operation costs were quite different between reamed and unreamed intramedullary nailing [1]. Our study showed that the re-operation rate was similar in the two treatment groups.…”
Section: Discussionmentioning
confidence: 45%
See 1 more Smart Citation
“…One study showed that there was no significant difference in the costs from the index procedure, index hospital stay, and fracture-associated medications; however, the re-operation costs were quite different between reamed and unreamed intramedullary nailing [1]. Our study showed that the re-operation rate was similar in the two treatment groups.…”
Section: Discussionmentioning
confidence: 45%
“…They can be classified into open and closed tibial fractures according to soft tissue injuries [1]. Open tibial fractures (OTF) are often associated with severe bone and soft tissue injury [2].…”
Section: Introductionmentioning
confidence: 99%
“…The extent and condition of soft tissue is a prerequisite for any management options [16,17]. Intramedullary nail is considered the optimal management choice in most case scenario [6,13,18,19], it is capable of providing early weight bearing and lower incidence of malalignment with less interference in the soft tissue of fracture site. Currently the indications for the IMN use is extending for distal tibial fractures with the improvement of nail design and application of a variety of the reduction techniques presented to minimize the malalignment such as poller screws and plateassistant reduction.…”
Section: Discussionmentioning
confidence: 99%
“…Injuries occurring here are classified based on soft tissue injury as open or closed. 1 Open tibial fractures are often associated with severe soft tissue and bone injury. 2 The management of open fractures is regarded as an orthopaedic emergency.…”
Section: Introductionmentioning
confidence: 99%